The Effect of Polyethylene Glycol Addition on Improving the Bioconversion of Cellulose - Kinga Szentner; Agnieszka Waśkiewicz; Robert Imbiorowicz; Sławomir Borysiak (Molecules)
In recent years, many studies have focused on improving the bioconversion of cellulose by adding non-ionic surfactants. In our study, the effect of the addition of a polymer, polyethylene glycol (PEG 4000), on the bioconversion of different cellulose materials was evaluated, focusing on the hydrolysis efficiency and structural changes in pure cellulose after the enzymatic hydrolysis process. The obtained results showed that the addition of non-ionic surfactant significantly improved the digestibility of cellulosic materials. The highest hydrolysis efficiency was observed for Sigmacel 101 (Cel-S101) cellulose, which consists mainly of amorphous regions. In the case of Avicel cellulose (Cel-A), PEG had a lesser effect on the bioconversion’s efficiency due to limited access to the crystal structure and limited substrate–cellulase interactions. The consistency of the obtained results is confirmed by qualitative and quantitative analyses (XRD, FTIR, and HPLC). Our findings may be helpful in further understanding the mechanism of the action of surfactants and improving the enzymatic hydrolysis process.